The Real Landscape Of Pulmonary Artery Hypertension Associated With Congenital Heart Disease In Vietnam National Heart Institute – Bach Mai Hospital – Vietnam - Thi Duyen Nguyen; Truong Thannh Huong (ACI (Acta Cardiologia Indonesiana), 2017)
The Real Landscape Of Pulmonary Artery Hypertension Associated With Congenital Heart Disease In Vietnam National Heart Institute – Bach Mai Hospital – Vietnam